Is open innovation imperative to small and medium enterprises?: A comparative study - Rahman, Md. Hakikur (2011)
The newly evolved trends of transformation in the entrepreneurships, their establishment, operation and management, and subsequent alterations in the entrepreneurship's knowledge arena has brought out the idea of open innovation, suggesting that ideas for innovations can transpire or go to market from outside the company as well as inside. Leaders among the global entrepreneurships, among others including researchers, academics and agencies acting as intermediaries are thriving to achieve success in accommodating open innovation (OI) strategies in their business processes or researches or activities leading to additional value gain. OI strategies, accepted by relatively large corporate business houses through their very nature, but as time passes and strategies mature, seemingly and gradually they are being adapted by the small and medium sized enterprises (SMEs) for the benefit of economic and knowledge gain. This paper through a comparative study has tried to incorporate ideas of open innovation that are suitable for SMEs and find answer to the question on the acceptance of OI strategies in SMEs.